Effects of Cold Stimulation Induced Pain on Cardiopulmonary Parameters: A Gender Based Study - Jha, R.K.; Amatya, S. (Kathmandu University Medical Journal, 2020)
Background Cold pressor induced pain elicits sympathetic responses which can be monitored by measuring blood pressure, heart rate and respiratory rate after exposure to the cold stress. Objective This study was done to evaluate gender difference in acute pain induced by cold pressor test on blood pressure, heart rate and respiratory rate of healthy individuals. Method Our study was cross sectional study with the sample size of 40 including 20 male and 20 female undergraduates. Acute pain was induced by immersion of hand in cold water at 4°C. Changes in blood pressure, heart rate and respiratory rate were recorded by the digital sphygmomanometer and AD Instruments (Model: ML856, Serial: T26-4025) and analysis was done by Lab Chart 7 Pro v 7.3.3 respectively. Acute pain parameter like pain threshold was also recorded. Statistical analysis was done by using Paired “t” test and non-parametric test. Result The present study enrolled 40 participants, aged between 18 – 24 years, and body mass index from 15.78 – 36.06 kg/m2. The respiratory rate was increased in both males (17.30±3.19 to 19.0±3.21, P=0.01) and females (18.60±1.98 to 19.90±2.82, P= 0.01) however significant increase in heart rate was only found in females (77.80±8.07 to 80.70±7.80, P=0.03) after cold pressor test. The systolic as well as diastolic blood pressure did not increase significantly after cold pressor test. The pain thresholds ranged from 25.2 to 105.8 seconds (61.60±23.26, male Vs. 52.69±18.49, female, p = 0.188). Conclusion Our findings point towards autonomic adjustments suggesting more of sympathetic over activity immediately after cold pressor test.